Hepatoprotection by L-Ornithine L-Aspartate in Non-Alcoholic Fatty Liver Disease - Roger F. Butterworth; Ali Canbay (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Background. Non-alcoholic fatty liver disease (NAFLD) is the leading chronic hepatic condition worldwide and new approaches to management and treatment are limited.Summary. L-ornithine L-aspartate (LOLA) has hepatoprotective properties in patients with fatty liver of diverse etiology and results of a multicenter randomized clinical trial reveal that 12 weeks treatment with oral LOLA (6–9 g/d) results in a dose-related reduction in activities of liver enzymes and triglycerides together with significant improvements of liver/spleen CT ratios. A preliminary report described improvements of hepatic microcirculation in patients with nonalcoholic steatohepatitis (NASH) following treatment with LOLA. Mechanisms responsible for the beneficial effects of LOLA in NAFLD/NASH involve, in addition to its established ammonia-lowering effect, metabolic transformations of the LOLA-constituent amino acids L-ornithine and L-aspartate into L-glutamine, L-arginine, and glutathione. These metabolites have well-established actions implicated in the prevention of lipid peroxidation, improvement of hepatic microcirculation in addition to anti-inflammatory, and anti-oxidant properties.Key messages. (1) LOLA is effective for the treatment of key indices in NAFLD/NASH. (2) Mechanisms other than LOLA’s ammonia-lowering action have been postulated. (3) Further assessments in the clinical setting are now required.